Carbon Nanotube Reinforced Structural Composite Supercapacitor - Muralidharan, Nitin (Sci Rep, 2018)
Carbon nanotubes exhibit mechanical properties ideally suited for reinforced structural composites and surface area and conductivity attractive for electrochemical capacitors. Here we demonstrate the multifunctional synergy between these properties in a composite material exhibiting simultaneous mechanical and energy storage properties. This involves a reinforcing electrode developed using dense, aligned carbon nanotubes grown on stainless steel mesh that is layered in an ion conducting epoxy electrolyte matrix with Kevlar or fiberglass mats. The resulting energy storage composites exhibit elastic modulus over 5 GPa, mechanical strength greater than 85 MPa, and energy density up to 3 mWh/kg for the total combined system including electrodes, current collector, Kevlar or fiberglass, and electrolyte matrix. Furthermore, findings from in-situ mechano-electro-chemical tests indicate simultaneous mechanical and electrochemical functionality with invariant and stable supercapacitor performance maintained throughout the elastic regime.